Quantitative risk assessment of the likelihood of importing mechanically recovered poultry meat contaminated with Salmonella into South Africa - Qekwana, Daniel Nenene (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2022.